COPING MECHANISM TOWARDS CAREGIVER ADAPTATION ABILITY IN CARING FOR CLIENTS WITH SCHIZOPHRENIA IN ACEH: A CROSS-SECTIONAL STUDY - Mohd. Rizal Fahmi Adha; Siti Nurafifah Qarimah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Caregivers who care for schizophrenic clients are at risk of experiencing psychological problems, one of which is high levels of stress, so good adaptation skills are needed. This study aims to determine the effect of threat coping on caregivers' adaptability in caring for schizophrenic clients in Aceh using a cross sectional study approach. The sampling technique used a multistage random sampling technique with a sample size of 180 respondents. Data collection uses instruments, namely demographic data which includes age, gender, marital status, education, employment, relationship with clients, and income. The next instruments are the Coping Scale and Occupational Adaptation Questionnaire of Family Caregiver (QAQC) to assess coping mechanisms on caregiver adaptation abilities. . The results showed that the majority of caregivers were women (97.8%), aged between 46 and 55 years (71.7%), marital status was widower (66.1%), the relationship between caregiver and patient was mother (69, 4%), basic income education (72.2%) and below the provincial minimum wage (83.3%). Bivariate tests showed that there was a relationship between coping mechanisms (p=0.024) and caregivers' adaptability in caring for schizophrenic clients (p=0.000). It can be concluded that coping mechanisms can influence caregivers' adaptability in caring for schizophrenic clients. It is recommended that the attention of Community Health Centers, especially Aceh, can provide important information in carCaregivers who care for schizophrenic clients are at risk of experiencing psychological problems, one of which is high levels of stress, so good adaptation skills are needed. This study aims to determine the effect of threat coping on caregivers' adaptability in caring for schizophrenic clients in Aceh using a cross sectional study approach. The sampling technique used a multistage random sampling technique with a sample size of 180 respondents. Data collection uses instruments, namely demographic data which includes age, gender, marital status, education, employment, relationship with clients, and income. The next instruments are the Coping Scale and Occupational Adaptation Questionnaire of Family Caregiver (QAQC) to assess coping mechanisms on caregiver adaptation abilities. . The results showed that the majority of caregivers were women (97.8%), aged between 46 and 55 years (71.7%), marital status was widower (66.1%), the relationship between caregiver and patient was mother (69, 4%), basic income education (72.2%) and below the provincial minimum wage (83.3%). Bivariate tests showed that there was a relationship between coping mechanisms (p=0.024) and caregivers' adaptability in caring for schizophrenic clients (p=0.000). It can be concluded that coping mechanisms can influence caregivers' adaptability in caring for schizophrenic clients. It is recommended that the attention of Community Health Centers, especially Aceh, can provide important information in caring for schizophrenic clients to their caregivers.ing for schizophrenic clients to their caregivers.